Hotels Service Selective Behaviors of Tourists at Muenwai Sub-district, Mueang District, Nakhon Ratchasima Province - Thanapiboonpong, Chitsanupong; Nilgumhaeng, Ramnarong (Journal of Management Science Nakhonratchasima University, 2022)
This study was aimed to study the behavior and the marketing mix factors affecting the tourists’ decisions in selecting the hotels in Muen Wai Sub-district, Mueang District, Nakhon Ratchasima Province. The researcher collected data from the sample group through an interview form. Purposive sampling method was employed in this study. The data were triangulated from 5 hotel business stakeholders, and 400 tourists who used the service from the 2 licensed hotels, given by the Ministry of Interior. The questionnaires were also used as the other data collection instrument. The data were analyzed by using the frequency, the percentage, the mean and the standard deviation. The hypothesis was tested by using t-test, F-Test and One-Way ANOVA. The individually differences were compared by using Least Significant Difference (LSD) and the correlation analysis was also employed by Pearson Product Moment Correlation Coefficient. The results showed that the tourists’ decisions in choosing the hotels, in Muen Wai Sub-district, was for the relaxation at the highest level. They received the information from the Internet. Majority of the tourists travelled by their own cars and stayed at the hotel during the weekend on Saturday and Sunday. The marketing factors , affecting the tourists’ decisions in selecting the hotel, were generally at the high level. For an individual aspect, it was found that the tourists considered the price as their first option and at the highest level in selecting the hotel